Cancer targeted drug delivery using active low-density lipoprotein nanoparticles encapsulated pyrimidines heterocyclic anticancer agents as microtubule inhibitors - Laila Jaragh-Alhadad; Haider Behbehani; Sadashiva Karnik (Taylor & Francis Group, 2022)
Recently, nanomedicine had the potential to increase the delivery of active compounds to specific cell sites. Nano-LDL particles are recognized as an excellent active nano-platform for cancer-targeted delivery. Loading of therapeutic agents into nano-LDL particles achieved by surface loading, core loading, and apolipoprotein-B100 interaction. Therefore, loading nano-LDL particles' core with pyrimidine heterocyclic anticancer agents will increase cancer cytotoxic activity targeting tubulin protein. First, by mimicking the native LDL particle's metabolic pathway, and second the agent's chemical functional groups like the native amino acids cytosine and thymine structures will not be recognized as a foreign entity from the cell's immune system. Nano-LDL particles will internalize through LDL-receptors endocytosis and transport the anticancer agent into the middle of the cancer cell, reducing its side effects on other healthy cells. Generally, the data revealed that pyrimidine heterocyclic anticancer agents' size is at the nano level. Agents' morphological examination showed nanofibers, thin sheets, clusters, and rod-like structures. LDL particles' size became bigger after loading with pyrimidine heterocyclic anticancer agents and ranged between 121.6 and 1045 nm. Then, particles were tested for their cytotoxicity against breast (MDA468) and prostate (DU145) cancer cell lines as surrogate models with dose-response study 10, 5, 1 µM. The IC50 values of the agents against DU145 and MDA468 possessed cell growth inhibition even at the 1 µM concentration ranges of 3.88 ± 1.05 µM and 3.39 ± 0.97 µM, respectively. In sum, nano-LDL particles proved their efficiency as active drug delivery vehicles to target tubulin in cancer cells.